Religious transformation and character: a phenomenological study of pesantren ramadan experience in high school - Sriwahyuni, Ranti Ayu; Fakhruddin, Agus; Surahman, Cucu (ATTARBIYAH: Journal of Islamic Culture and Education, 2025)
As modernisation accelerates and religious engagement among adolescents declines, there is an urgent need for Islamic education models that prioritise meaningful character transformation over mere cognitive instruction. This study examines the transformative impact of religiosity and character development on students and teachers participating in the Pesantren Ramadan (SMARTTREN) program at a public high school in Bandung. Using a qualitative phenomenological approach, data were collected through observations, in-depth interviews, and document analysis. The findings indicate that SMARTTREN functions as a comprehensive learning environment that fosters spiritual, social, and moral development. Teachers view the program as a means of role modelling and spiritual renewal. Concurrently, students reported increased discipline in worship, a stronger emotional and spiritual connection to Allah, and noticeable positive changes in their daily interactions. These results suggest that SMARTTREN is an effective contextual model of Islamic education in public schools, providing sustainable pathways to enhance students' religiosity and character formation. The program has significant potential for replication and integration into curricula in similar educational settings.